Differential Expression of Myogenic and Calcium Signaling-Related Genes in Broilers Affected With White Striping - Marciano C.M.M.* (2021)
© Copyright © 2021 Marciano, Ibelli, Marchesi, de Oliveira Peixoto, Fernandes, Savoldi, do Carmo and Ledur.White Striping (WS) has been one of the main issues in poultry production in the last years since it affects meat quality. Studies have been conducted to understand WS and other myopathies in chickens, and some biological pathways have been associated to the prevalence of these conditions, such as extracellular calcium level, oxidative stress, localized hypoxia, possible fiber-type switching, and cellular repairing. Therefore, to understand the genetic mechanisms involved in WS, 15 functional candidate genes were chosen to be analyzed by quantitative PCR (qPCR) in breast muscle of normal and WS-affected chickens. To this, the pectoral major muscle (PMM) of 16 normal and 16 WS-affected broilers were collected at 42 days of age and submitted to qRT-PCR analysis. Out of the 15 genes studied, six were differentially expressed between groups. The CA2, CSRP3, and PLIN1 were upregulated, while CALM2, DNASE1L3, and MYLK2 genes were downregulated in the WS-affected when compared to the normal broilers. These findings highlight that the disruption on muscle and calcium signaling pathways can possibly be triggering WS in chickens. Improving our understanding on the genetic basis involved with this myopathy might contribute for reducing WS in poultry production.